Improvement of the Assets of Commercial Banks - Norov Akmal Ruzimamatovich; Nazarova Muslima Nazarovna; Abdusattarova Shaxida Abutalipovna; Beknazarova Nilufar Tulkinovna; Akbarov Husniddinjon Mo’ysino’g’li (International Journal on Economics, Finance and Sustainable Development, 2021)
The article examines the improvement of the quality of assets of commercial banks and the factors influencing it on the basis of theoretical and practical data. Also, based on the study of foreign experience, it is argued that the increase in asset quality in banks will directly improve the quality of credit services provided by banks, reduce problem loans and the use of credit scoring system. A number of specific aspects of the use of credit scoring system in improving the quality of assets of commercial banks have been studied in detail on the basis of theoretical and practical data, scientific proposals and practical recommendations have been developed on the basis of author's approaches.